The effect of central sensitization on interlaminar epidural steroid injection treatment outcomes in patients with cervical disc herniation: an observational study - SAÇAKLIDIR, REKİB; ŞANAL TOPRAK, CANAN; GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (My University, 2022)
© 2022, American Society of Interventional Pain Physicians. All rights reserved.Background: Central sensitization (CS) is a hyperexcitability that is manifested by the increased response of the central nervous system to sensory stimuli. It has been shown that the presence of CS may have a negative effect on the clinical picture in some musculoskeletal diseases and also have a negative effect on spinal procedures. Objectives: To investigate the effect of CS on interlaminar epidural steroid injection (ILESI) treatment outcomes in patients with cervical disc herniation (CDH). Study Design: An observational study. Setting: A university hospital pain management center. Methods: Patients, who underwent ILESI between 2020-2021 due to CDH, were included in the study. The Numeric Rating Scale (NRS-11), Neck Pain and Disability Scale (NPDS), Self-Administered Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS), and Short Form-12 (SF-12) were used for evaluation of patients. Patients were assessed before the procedure, at the first hour, and 3 months after the procedure. The presence of CS was investigated by the Central Sensitization Inventory (CSI). Results: A total of 51 patients were included in the study. Twenty-three of the patients had CS, as assessed by the CSI. Although, patients who underwent ESI, had significantly lower NRS-11, S-LANSS, and NPDS scores, and higher SF-12 scores at all follow-up points. The first and third months, NRS-11, S-LANSS, and NPDS were significantly higher, and SF-12 scores were lower in the CS group compared to patients without CS. Limitations: The short follow-up period and relatively low number of patients can be considered as a limitation. The fact that CS is not evaluated with a more objective method, such as Quantitative Sensory Testing (QST), can be considered as another limitation. Since most clinicians use CSI, so from a \"real world\" perspective the lack of QST may be observed as a strength of the study. The third limitation is that we did not evaluate the patients’ pre-and posttreatment analgesic consumption. Finally, we did not include patients with a history of psychiatric illness, but not evaluating the current psychiatric conditions of the patients could be considered a limitation. Nevertheless, the main strengths of this study are its prospective design and, to our knowledge, it is the first study to explore the effects of CS on cervical ESI treatment. Conclusions: The presence of CS has a negative effect on pain scores, disability, and quality of life in patients undergoing cervical ESI due to CDH.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; central sensitization; central sensitization inventory; Cervical disc herniation; epidural injections; interlaminar; neck pain; steroids; treatment success; Cervical disc herniation; epidural injections; central sensitization; central sensitization inventory; neck pain; treatment success; interlaminar; steroids